History of Islamic Civilization in Post-Independence Indonesia - Nabila Nurazizah; Ima Halimatusadiah; Imam Tabroni; Mahon Nitin; Snyder Bradford (Yayasan Adra Karima Hubbi, 2023)
Background. Islam is a religion that prioritizes the principles of truth and justice for all its adherents. Factors that encourage Muslims to achieve independence are ideological, political, economic, social and cultural factors. Islam has an important role in the development of education in Indonesia. There are three sectors of Islamic education in Indonesia, namely formal, informal and non-formal. Purpose. The purpose of this research is to find out 1.) The history of the development of Islam in Indonesia after independence. 2.) The impact of the development of Islam in Indonesia. 3.) The process of development of Islamic civilization. So from the description above, the author will explain how the development of Islam in Indonesia after independence, what caused the emergence of the Islamic renewal movement, especially in Indonesia. Method. This research uses the type of literature study (library research). The data collection technique carried out in this study uses a study of bibliographic sources from books and articles in scientific journals related to the subject matter, reading data with the thoughts of experts with a constructive approach and interpretation of the contents of the main discussion related to the development of Islam after independence. Results. After Indonesia's independence in 1945, Islamic civilization in the country continued to develop and made significant contributions in various aspects of life. Conclusion. After independence, Islamic education was one of the key points in the development of Islamic civilization in Indonesia. The thinking and writing of Indonesian Islamic intellectuals also developed with many studies, writings and translations of classical and modern Islamic works. The Salafi movement that insists on returning to the teachings of Islam is considered to be fully associated with the salafushalih (early generations of Islam), and emerged and developed after independence.